APPLICATION OF IMAGE MEDIA IN TEACHING SCIENCE TO CLASS 5 STUDENTS AT SDN 7 LINGE CENTRAL ACEH - Rosnawati, Siti; Sari, Siti Mayang (Sensei International Journal of Education and Linguistic, 2024)
Education plays a fundamental role in shaping the character and competence of the younger generation, with learning media being a crucial element in this process. Natural Science (Science) subjects with their complexity of concepts require effective and innovative teaching strategies to facilitate student understanding. It is hoped that the use of image media can create a dynamic, interactive learning atmosphere and support a holistic understanding of science concepts. This research aims to describe the application of image media in teaching science to grade 5 students at SDN 7 Linge Central Aceh. This research uses a qualitative approach with descriptive research type. Based on the results of research conducted at SDN 7 Linge, grade 5 teachers have succeeded in implementing image media integration strategies effectively in science learning. Through group assignments or student projects, teachers give them the freedom to create presentations using relevant image media and which support the science concepts being studied. Despite the challenges faced by the diversity of students' learning styles and technology skill levels, teachers continue to look for creative solutions, with a focus on evaluating the effectiveness of using image media.